2021
DOI: 10.48550/arxiv.2108.08730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate 3D frequency-domain seismic wave modeling with the wavelength-adaptive 27-point finite-difference stencil: a tool for full waveform inversion

Abstract: Efficient frequency-domain Full Waveform Inversion (FWI) of long-offset/wide-azimuth node data can be designed with a few discrete frequencies. However, 3D frequency-domain seismic modeling remains challenging since it requires solving a large and sparse linear indefinite system per frequency. When such systems are solved with direct methods or hybrid direct/iterative solvers, based upon domain decomposition preconditioner, finite-difference stencils on regular Cartesian grids should be designed to conciliate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The second discretization scheme relies on the 27-point finite-difference stencil on regular Cartesian grid (constant grid interval h) in which compact 2 nd -order accurate stencils minimize the numerical bandwidth and maximizes the sparsity of A while reaching a high-order accuracy by mixing consistent mass and stiffness matrices on different (rotated) coordinate systems (Aghamiry et al, 2021;Brossier et al, 2010;Chen et al, 2012;Operto et al, 2014Operto et al, , 2007. These sparsity and compactness properties are useful to minimize the matrix fill-in induced by a sparse direct solver, which is used to solve the local problems in each subdomain of the preconditioner.…”
Section: Finite-difference Frequency-domain (Fdfd) Discretizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The second discretization scheme relies on the 27-point finite-difference stencil on regular Cartesian grid (constant grid interval h) in which compact 2 nd -order accurate stencils minimize the numerical bandwidth and maximizes the sparsity of A while reaching a high-order accuracy by mixing consistent mass and stiffness matrices on different (rotated) coordinate systems (Aghamiry et al, 2021;Brossier et al, 2010;Chen et al, 2012;Operto et al, 2014Operto et al, , 2007. These sparsity and compactness properties are useful to minimize the matrix fill-in induced by a sparse direct solver, which is used to solve the local problems in each subdomain of the preconditioner.…”
Section: Finite-difference Frequency-domain (Fdfd) Discretizationmentioning
confidence: 99%
“…Alternatively, G can be first tabulated such that it covers the range of values found in the earth and the corresponding table of weighting coefficients are estimated once and for all by minimizing the phase-velocity numerical dispersion for each value of G treated separately (the weights become functions of G). Then, for a simulation at a given frequency f , each row of the matrix A (which is tied to a given grid point) is built by picking in the table the weights corresponding to the local G = λ/h hence leading to the λ-adaptive 27-point stencil (Aghamiry et al, 2021). We will use the latter in this study since Aghamiry et al (2021) showed that the λ-adaptivity increases the accuracy of the 27-point stencil quite significantly in heterogeneous media, in particular in presence of sharp contrast.…”
Section: Finite-difference Frequency-domain (Fdfd) Discretizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our rationale behind the choice of the polynomial order is to choose the coarsest discretization providing the desired accuracy while being able to capture heterogeneities during FWI whose size is of the order of half the wavelength, namely the theoretical resolution of FWI . The second discretization scheme relies on the recently proposed compact wavelength-adaptive 27point finite-difference method on uniform Cartesian grid (Aghamiry et al, 2021). The governing idea of this method compared to the classical 27-point stencil (Operto et al, 2007) is to make its accuracy uniform with respect to the local wavelength through a local adaptation of the stencil coefficients.…”
Section: Introductionmentioning
confidence: 99%